Report of the Secretary of War, communicating; in compliance witha resolution of the Senate, a map showing the operations of the army of the United States in Texas and the adjacent Mexican Stateson the Rio Grande, accompanied by astronomical observations, and descriptive and military memoirs of the country. - U.S. War Departament., (2015)
UANL